(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda-The traditional medicinal science in India has holistic approach and practiced widely in the subcontinent. Large parts of the Ayurvedic drugs are heromineral preparations. These preparations are broad spectrum as far as its indications are concerned. Definite mode of action of these drugs are inexplicable. Vyadhividhwansana Rasa is an herbomineral preparation used for treating acute fever, interrupted fever, fever of unknown origin, ascites, splenomegaly, colic pain, Vata vyadhi, Aama jwara (first stage of fever) and Vishama jwara (irregular fever). In view of its therapeutic indications an antimicrobial study was designed to ascertain its probable mode of action. The present study aims to evaluate the antimicrobial activity of Vyadhividhwansana Rasa against test organisms at different concentration. Vyadhividhwansana Rasa was prepared as per Ayurvedic texts. Positive control Streptomycin [5mg(w/v)] and negative control 20% dimethyl sulfoxide (DMSO) were prepared. Solution of Vyadhividhwansana Rasa were prepared in three concentrations at 50 mg/ml, 100 mg/ml and 150 mg/ml in DMSO and was tested for its antimicrobial activity against Escherichia coli, Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella typhi by agar-well diffusion method. The measured Inhibition Zone ranged from 4-34 mm for all the sensitive bacteria. All the bacteria except Salmonella typhi were found Susceptible (S) against Vyadhividhwansana Rasa compared to standard. Salmonella typhi was found Intermediate sensitive (I). The antimicrobial activity of the extracts increased when the solution is more concentrated.